2011
DOI: 10.1039/c0an01038c
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for ranitidine hydrochloride determination in aqueous solution based on fluorescence quenching of functionalised CdS QDs through photoinduced charge transfer process: Spectroscopic approach

Abstract: A novel method for the quantitative determination of ranitidine hydrochloride (RNH) based on the fluorescence quenching of functionalised CdS quantum dots (QDs) by RNH in aqueous solution was proposed. The method is simple, rapid, specific and highly sensitive with good precision. The thioglycolic acid (TGA)-capped CdS QDs were synthesized from cadmium nitrate and sodium sulfide in alkaline solution. Under the optimal conditions, the Stern-Volmer calibration plot of F(0)/F against concentration of RNH was line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In this connection, many mechanisms have been proposed for the design of sensors for various analytes, such as inorganic ions [37,38,[53][54][55][56][57], biomolecules [22,30,33] and active pharmaceutical ingredients [34,35] based on the surface states fluorescence modulation of QDs. Similarly, herein we have suggested that same approach can also be utilized for turn-on sensing of d-PA based on MPA-CdS QDs.…”
Section: Possible Sensing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, many mechanisms have been proposed for the design of sensors for various analytes, such as inorganic ions [37,38,[53][54][55][56][57], biomolecules [22,30,33] and active pharmaceutical ingredients [34,35] based on the surface states fluorescence modulation of QDs. Similarly, herein we have suggested that same approach can also be utilized for turn-on sensing of d-PA based on MPA-CdS QDs.…”
Section: Possible Sensing Mechanismmentioning
confidence: 99%
“…Recently, our group has presented a novel approach to detect the vitamin B-12 by CdS QDs FRET probe [33]. We have also reported a novel method for the quantitative determination of ranitidine hydrochloride (RNH) based on the fluorescence quenching of functionalized CdS quantum dots in aqueous solution [34]. Recently, an automated multi-pumping flow system is proposed for the chemiluminometric determination of ascorbic acid in pharmaceutical formulations by Sasaki et al [35].…”
Section: Introductionmentioning
confidence: 98%
“…The value of zeta ( ) potential measured on zeta size is −15.7 mV confer high level stability of nanoparticles. The aqueous suspension of nanoparticle with high zeta potential (negative or positive) is electrically stabilized while those with low zeta potentials tend to coagulate or flocculate [30,31]. Scanning electron microphotograph (SEM) shown in Fig.…”
Section: Preparation Of N-methyl Isatin Nanoparticles (N-minps)mentioning
confidence: 99%
“…Among the various metal nanoparticles, AgNPs have been widely investigated because they exhibit unusual optical, electronic and chemical properties, depending on their size and shape with respect to technological applications [5]. The metal enhanced fluorescence (MEF) have attracted significant interest due to the widespread use of molecular fluorescence based measurements and devices in chemistry, molecular biology, material science, photonics and medicine [6,7]. However, the strength of enhancement or quenching might be influenced by many factors such as size and shape of metal NPs and several other factors which are of interest to be explored.…”
Section: Introductionmentioning
confidence: 99%